2007
DOI: 10.2500/aap.2007.28.3020
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-type hypersensitivity (type IV) reactions in dental anesthesia

Abstract: The recommended methodology of evaluating patients who have presented with reactions to local anesthetics consists of epicutaneous skin testing and serial subcutaneous challenge. However, the role of type IV reactions in this group has been poorly documented. Epicutaneous routine testing and subcutaneous challenge to local anesthetic was performed, as well as patch testing and subcutaneous rechallenge of both at 24 and 48 hours with evaluation up to 72 hours was performed. Three patients presented with a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Individuals allergic to lidocaine can tolerate ester-type local anesthetics. 8 Our experience in this case suggests that estertype local anesthetics are useful for patients with a history of allergic reactions to amide-type local anesthetics.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Individuals allergic to lidocaine can tolerate ester-type local anesthetics. 8 Our experience in this case suggests that estertype local anesthetics are useful for patients with a history of allergic reactions to amide-type local anesthetics.…”
Section: Discussionmentioning
confidence: 73%
“…6,7 However, a previous study suggested that individuals allergic to lidocaine could tolerate ester-type anesthetics. 8 Herein, we report a case in which effective dental anesthesia was achieved using procaine hydrochloride in a patient who had an unknown history of allergic reactions to amide-type local anesthetics, ie, lidocaine and propitocaine (prilocaine). Furthermore, we discuss the effective control of pain perception in patients with an unknown history of allergy to amide-type local anesthetics during dental treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin patch testing for allergy should always be considered in recalcitrant cases and in cases with suspected allergic induction (10). It is estimated that 5% of patients who use topical benzocaine preparations may become sensitized to it and, thus, long-term use can result in increased incidence of hypersensitivity reactions (<1% of all adverse reactions) (11). Most of these reactions are T cell-mediated type IV delayed hypersensitivity reactions, including allergic contact dermatitis confi rmed by skin patch tests.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that an immediate type IV hypersensitivity reaction to lidocaine occurred in these patients. 3,5 It may be impractical to avoid the repeated use of LLA in patients undergoing multiple surgeries, and in any case, a cross reaction between these two main classes of anaesthetic drugs may still occur. 5 What is important is to recognise the possibility of this complication, advise patients accordingly, and have corticosteroids on hand to limit the severity of the inflammatory reaction and ameliorate the progression of necrosis, should it appear.…”
mentioning
confidence: 99%